Photodegradation of cyprodinil under UV–visible irradiation – chemical and toxicological approaches. (5th September 2016) - Nicol, Edith; Chayata, Houda; Genty, Christophe; Bouchonnet, Stéphane; Bourcier, Sophie
Abstract : Rationale: Cyprodinil is a fungicide active on grapes, strawberries, tomatoes, and many other fruits. Under UV–visible irradiation, it undergoes photodegradation through various processes to form transformation products (TPs) whose structures and potential toxicities are unknown. The structures of the TPs were elucidated by comparing the photodegradation of cyprodinil and cyprodinil‐D5 . The potential toxicities of these compounds were compared with that of cyprodinil. Methods: Aqueous solutions of cyprodinil were irradiated in a reactor equipped with a mercury vapor lamp. Analyses were carried out using high‐performance liquid chromatography coupled to a quadrupole time‐of‐flight (QTOF) mass spectrometer or to a SolarixXR 9.4 Tesla Fourier transform (FT) mass spectrometer. High‐resolution mass measurements, MS/MS and isotopic labeling experiments allowed structural elucidation of the cyprodinil TPs. The toxicities were estimated by three tests in silico using the TEST software and in vitro bioassays using Vibrio fischeri bacteria. These bioassays were carried out on irradiated solution for several exposure times and non‐irradiated solutions. Results: The structures of 19 photoproducts were characterized by LC/HRMS/MS after 4 h of irradiation of a cyprodinil aqueous solution. The use of cyprodinil‐D5 allowed the TPs to be characterized with more confidence. Knowing the structure of the TPs allows the estimation of their potential toxicities by in silico tests. Most of the photoproducts are potentially more toxic than the parent compound, based on the oral rat LD50 values, and most of them might induce more developmental and mutagenic toxicities. In vitro assays on Vibrio fischeri bacteria showed that the global ecotoxicity of the cyprodinil solution significantly increases with irradiation time. Conclusions: Structures of photoproducts were characterized after irradiation of a cyprodinil aqueous solution combining LC/HRMS, LC/HRMS/MS and the use of a labeled compound. Their formations imply several photodegradation reactions, namely direct bond cleavages, cyclization, isomerization and hydroxylation. Most of the TPs exhibit a toxicity significantly higher than that of the parent molecule. Copyright © 2016 John Wiley & Sons, Ltd.